Public Company Auditor Changes and Big Eight Firms: Disagreements and Other Issues (Book). - Campbell, Terry L.; Hendrickson, Harvey S. (The Accounting Review, 1984)
Reviews the book "Public Company Auditor Changes and Big Eight Firms: Disagreements and Other Issues," by Donald K. McConnell.